Increasing Teachers’ Capacity To Use ICT and TPACK-Based PJOK Learning - Hukubun, Mariana Ditboyo; Solissa, Jonas; Hattu, Mesak; Souisa, Mieke (Universitas Pattimura, 2024)
A community service activity will be carried out with the aim of: (1) Physical education teachers being able to create practical learning videos themselves; (2) Physical education teachers being able to create theoretical learning videos using Microsoft Office Power Point. The target group for this activity are former and volunteer physical education, sport and health teachers at junior high school and high school level in the Aru Islands Regency, a total of 20 people. While the method adopted in this community service activity is; (1) problem identification, (2) preparation and debriefing, (3) implementation of activities, and (4) programme continuity plan. Furthermore, the results obtained are based on structured independent tasks for the participants who are divided into 5 large groups to complete practical and theoretical learning videos using Microsoft office power point, namely; (1) only 1 out of 4 groups was able to complete the practical learning videos, and (2) for the theoretical learning videos, 4 groups were able to complete them well while 1 group could not complete the task. Therefore, it can be concluded that after the community service activities, the participants were generally able to produce both practical and theoretical learning videos using Microsoft Office Power Point.